Effect of use residual sludge from watertreatment plants as a partial substitute forclay for refractory bricks production (2020)
The sludge generated from water treatment has been classified as a potential environmental pollutant. Because of its chemical composition similar to clay, was proposed to evaluate the effect of its incorporation as a partial substitute for traditional clay materials in the manufacture of aluminosilicate refractory bricks. The raw materials used were characterized by XRD and XRF; the prototypes designed were mixed, extruded, dried and firing at 1200 °C, evaluating their linear shrinkage, apparent density, porosity, water absorption and mechanical and pyroscopic resistance (melting cone softening point). The results show the addition of 10% of sludges from industrial water treatment plant, contributed to elevate the softening point the clay that obtaining a refractory brick capable to supporting a temperature up to 1430 °C.